2018
DOI: 10.1080/24750573.2018.1445898
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Temporal Satisfaction with Life Scale among Turkish people

Abstract: OBJECTIVES:The determinants of subjective well-being have been largely investigated in recent years. According to Pavot and Diener who have developed TSWL (Temporal Satisfaction with Life Scale), to assess the life satisfaction level of an individual according to temporal factors, subjective well-being is composed of two constructs: an emotional or affective component (i.e. positive and negative affects) and a conceptual or cognitive component (i.e. satisfaction with life, marriage, work, and leisure). The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…= .91 overall, ! = .81 present; Tomás et al, 2016), with a test-retest reliability of 0.81 (Akyurek et al, 2019). The reliability of the Present subscale in our sample was similarly high (!…”
Section: Life Satisfactionsupporting
confidence: 58%
“…= .91 overall, ! = .81 present; Tomás et al, 2016), with a test-retest reliability of 0.81 (Akyurek et al, 2019). The reliability of the Present subscale in our sample was similarly high (!…”
Section: Life Satisfactionsupporting
confidence: 58%
“…In addition, although individual and cultural differences affect the results, it is possible to evaluate the LS of an individual by measuring the domain satisfaction (work, friendship, health, etc. ;Akyürek et al, 2019). Consequently, the Riverside Life Satisfaction Scale (RLSS) was developed by Margolis et al (2019).…”
Section: Sage Openmentioning
confidence: 99%
“…In addition to having been used less often than the SWLS, the TSWLS's psychometric properties have rarely been investigated. Specifically, only eight studies, including the original study by Pavot et al ( 1998 ), have investigated the psychometric properties of this scale, and this has been across vastly different cultures and languages in the different countries of Turkey (Akyurek et al, 2019 ), Canada (McIntosh's, 2001 ), China (Ye, 2007 ), Germany (Trautwein, 2004 ), Spain (Tomás et al, 2016 ; Carrillo et al, 2021 ), Switzerland (Proyer et al, 2011 ), United-States (Pavot et al, 1998 ), and in different populations, such as undergraduate students (e.g., McIntosh's, 2001 ), adults (e.g., Akyurek et al, 2019 ), and older adults (e.g., Carrillo et al, 2021 ). Moreover, of those studies, only Pavot et al ( 1998 ) and McIntosh's ( 2001 ) were conducted using the original English version; all other studies used various non-English adaptations of the scale (i.e., Chinese, German, Spanish, Swiss, Turkish).…”
Section: Introductionmentioning
confidence: 99%
“…Their results supported a three-factor structure which includes all 15 original items. The Turkish adaptation of the scale was found to have a better fit with the first item of each five-item subscale removed, resulting in a 12-item measure (Akyurek et al, 2019 ), whereas the Chinese adaptation was found to have a better fit with the first and last items of each 5-item subscale removed, with then each subscale resulting in 3-items and in a 9-item measure (Ye, 2007 ). Thus, it appears there are unresolved issues regarding the replicability of the validity of the scale structure and optimal number of items.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation